Determinants of Secondary Market Prices for Developing Country Syndicated Loans. - Boehmer, Ekkehart; Megginson, William L (Journal of Finance, 1990)
This paper presents the authors' investigation of the factors that determine secondary market prices of developing country syndicated loans. Trading volume in this market has almost doubled yearly from 1985 to 1988, while average market prices declined from 73 percent to 41 percent of par value during the same period. The authors find that loan values depend on a country's solvency rather than its liquidity and show that a country's adoption of a debt-conversion program significantly decreases its loans' market prices. Furthermore, the debt moratoria by Brazil and Peru, as well as the developing-country-specific provisions made by U.S. banks, impact loan prices negatively.